Incidence and prevalence of tuberculosis in systemic lupus erythematosus patients: A systematic review and meta-analysis - Wu, Qian; Liu, Yang; Wang, Wei; Zhang, Yu; Liu, Kui; Chen, Song-Hua; Chen, Bin (Frontiers in Immunology, 2022)
Background Systemic lupus erythematosus (SLE) patients are particularly susceptible to infections, such as pulmonary tuberculosis (PTB) and extrapulmonary tuberculosis (EPTB). This meta-analysis aimed to determine the incidence and prevalence of tuberculosis (TB) in SLE patients. Methods The Web of Science, PubMed, Cochrane Library, and Chinese National Knowledge Infrastructure databases were searched for articles of relevant studies published from the dates the databases were established until April 30, 2022. The I2 statistic and Q test were used to evaluate heterogeneity among the analysed studies. Random-effects models were utilised and subgroup analyses were conducted for analysis of the study data. Results A total of 35 studies with 46,327 SLE patients were eligible for analysis. The incidence and prevalence of TB among the SLE patients were 1.16 per 100 person-years (95% confidence interval (CI): 0.69-1.93) and 3.59% (95% CI: 2.57%-5.02%), respectively. The pooled prevalence of SLE-PTB and SLE-EPTB was 2.46% (95% CI: 1.73%-3.51%) and 1.42% (95% CI: 0.98%-2.06%), respectively. Subgroup analyses showed that the incidence of SLE-TB was higher in Africa and in countries with a high TB burden than in countries with a low TB burden. The prevalence of SLE-TB was elevated in Asia, in patients taking a mean daily dose of glucocorticoids ≥20 mg, in studies with small sample sizes (n <1000) and ended before 2001. Conclusions The available evidence suggests that both the incidence and prevalence of TB in SLE patients are high. This study provides a more specific understanding of SLE-TB, which can help health policymakers in the development of preventive strategies for reducing the SLE-TB burden.